25.5k views
0 votes
Drag each equation to show if it could be a correct first step to solving the equation

4(3 + x)=36



4(3+x)=144
(4•3)+(4•x)=36
12+4x=36
12+x=36
3+4x=36
3+x=9

Yes,no,not enough

2 Answers

7 votes

Answer:

yw

Explanation:

Drag each equation to show if it could be a correct first step to solving the equation-example-1
User Zerg Overmind
by
5.9k points
4 votes

Answer:

x=6

Explanation:

4(3+x)=36

12+4x=36

4x=36-12

4x=24

x=6

Proof: 4(3+x)=36

4(3+6)=36

12+24=36

36=36

Hope it helps

User Tim Gage
by
6.1k points